A combination of solid-state NMR and MD simulations reveals the binding mode of a rhomboid protease inhibitor. Issue 38 (6th September 2021) - Bohg, Claudia; Öster, Carl; Utesch, Tillmann; Bischoff, Susanne; Lange, Sascha; Shi, Chaowei; Sun, Han; Lange, Adam
Abstract : Proton-detected solid-state NMR in combination with molecular docking and molecular dynamics (MD) simulations allow the study of rhomboid protease inhibition under native-like conditions. Abstract : Intramembrane proteolysis plays a fundamental role in many biological and pathological processes. Intramembrane proteases thus represent promising pharmacological targets, but few selective inhibitors have been identified. This is in contrast to their soluble counterparts, which are inhibited by many common drugs, and is in part explained by the inherent difficulty to characterize the binding of drug-like molecules to membrane proteins at atomic resolution. Here, we investigated the binding of two different inhibitors to the bacterial rhomboid protease GlpG, an intramembrane protease characterized by a Ser–His catalytic dyad, using solid-state NMR spectroscopy. H/D exchange of deuterated GlpG can reveal the binding position while chemical shift perturbations additionally indicate the allosteric effects of ligand binding. Finally, we determined the exact binding mode of a rhomboid protease-inhibitor using a combination of solid-state NMR and molecular dynamics simulations. We believe this approach can be widely adopted to study the structure and binding of other poorly characterized membrane protein–ligand complexes in a native-like environment and under physiological conditions.